THE ANTIBACTERIAL EFFECTIVENESS OF SEAWEED (Eucheuma cottonii) EXTRACT ON Bacillus cereus and Pseudomonas aeruginosa - Hutabarat, M. Aziz Amin; Sari, N. Ira; Leksono, Tjipto (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
The aim of the research was to assess the antibacterial effectiveness of seaweed Eucheuma cottonii extract as inhibitor to the growth of Bacillus cereus and Pseudomonas aeruginosa and to determine the minimum inhibitory concentration of Eucheuma cottonii extract on Bacillus cereus and Pseudomonas aeruginosa. The method used was the experimental. The most effective concentration of the extract was 6% that could inhibit the growth of Bacillus cereus with a clear zone of 6 mm. Meanwhile, the extract concentration of 4% was the effective concentration to inhibit the growth of Pseudomonas aeruginosa with a clear zone of 5 mm.Keywords : antibacterial, Bacillus cereus, Pseudomonas aeruginosa, seaweed